وعى الأسرة ومدى إستفادتها من برامج وأنشطة وخدمات المراكز والجمعيات المختلفة التى تخدم الأسرة - مليبارى، نجاة عبدالله محمد Malibari, Najah Abdullah Mohammed (جامعة عين شمس - كلية التربية - الجمعية المصرية للقراءة والمعرفة, 2016)
تهدف الدراسة إلى التعرف على التعرف على مدي وعي الأسرة ومدي استفادتها من برامج وأنشطة وخدمات المراكز والجمعيات المختلفة التي تخدم الأسرة, والكشف عن العلاقة الارتباطية بين وعي الأسرة بوجود خدمات تقدمها المراكز والجمعيات المختلفة واستفادتها من البرامج والأنشطة والخدمات التي تقدمها المراكز والجمعيات المختلفة, وقد طبقت أدوات الدراسة "استمارة البيانات العامة, استبيان وعي الأسرة ومدي استفادتها من برامج وأنشطة وخدمات المراكز والجمعيات المختلفة التي تخدم الأسرة" على عينة البحث وقوامها (230) أسرة من مستويات اجتماعية واقتصادية مختلفة وقد توصلت الدراسة إلي: • أن مستوي الوعي المرتفع بوجود خدمات تقدمها المراكز كان يمثل نسبة 29.1 %، بينما مستوي الوعي المتوسط بوجود خدمات تقدمها المراكز كان يمثل نسبة 48.3 %، في حين أن مستوي الوعي المنخفض بوجود خدمات تقدمها المراكز كان يمثل نسبة 22.6 %، كما يتضح من الجدول والشكل البياني أن مستوي الاستفادة المرتفعة من الخدمات التي تقدمها المراكز كانت يمثل نسبة 37.8 %، بينما مستوي الاستفادة المتوسطة من الخدمات التي تقدمها المراكز كانت يمثل نسبة 41.3 %، في حين أن مستوي الاستفادة المنخفضة من الخدمات التي تقدمها المراكز كانت يمثل نسبة 20.9 %. • فروق ذات دلالة إحصائية بين أفراد العينة في الوعي بوجود خدمات تقدمها المراكز والجمعيات المختلفة تبعا لمتغيرات الدراسة "الحالة الاجتماعية، تعليم الزوج والزوجة، عمر الزوجة، عمل الزوجة، الدخل الشهري للأسرة"، فكانت دالة لصالح المتزوجات، والمستوي التعليمي للزوج والزوجة، وللعمر الأكبر، وللزوجات العاملات، ولأفراد الأسرة ذوي والدخل المتوسط. • فروق ذات دلالة إحصائية بين أفراد العينة في الوعي بوجود خدمات تقدمها المراكز والجمعيات المختلفة تبعا لمتغيرات الدراسة "الحالة الاجتماعية، تعليم الزوج والزوجة، عمر الزوجة، عمل الزوجة، الدخل الشهري للأسرة"، فكانت دالة لصالح المتزوجات، والمستوي التعليمي للزوج والزوجة، وللعمر الأكبر، وللزوجات العاملات، ولأفراد الأسرة ذوي والدخل المتوسط. • فروق ذات دلالة إحصائية بين افراد العينة في الاستفادة من البرامج والأنشطة والخدمات التي تقدمها المراكز والجمعيات المختلفة تبعا لمتغيرات الدراسة الحالة الاجتماعية تعليم الزوج والزوجة عمر الزوجة عمل الزوجة الدخل الشهري للأسرة فكانت دالة لصالح المتزوجات والمستوى التعليمي للزوج والزوجة وللعمر الأكبر وللزوجات العاملات ولافراد الاسرة ذوي والدخل المنخفض • وجود علاقة ارتباطية طردية بين وعي الاسرة بوجود خدمات تقدمها المراكز والجمعيات المختلفة واستفادتها من البرامج والأنشطة والخدمات التي تقدمها المراكز والجمعيات المختلفة • تختلف نسبة مشاركة العوامل المؤثرة على وعي الاسرة بوجود خدمات تقدمها المراكز والجمعيات المختلفة حيث كان تعليم الزوجة في المرتبة الأولى يليه عمر الزوجة في المرتبة الثانية ثم تعليم الزوج في المرتبة الثالثة وأخيرا الدخل الشهري للاسرة في المرتبة الأخيرة • تختلف نسبة مشاركة العوامل المؤثرة على استفادة الاسرة من البرامج والأنشطة والخدمات التي تقدمها المراكز والجمعيات المختلفة حيث كان تعليم الزوج في المرتبة الأولى يليه تعليم الزوجة في المرتبة الثانية ثم عمر الزوجة في المرتبة الثالثة وأخيرا الدخل الشهري للاسرة في المرتبة الأخيرة وقد اوصت الدراسة ب: عقد ندوات تثقيفية ودورات تدريبية لتوعية الاسرة بأهمية الاستفادة مما تقدمة المراكز والجمعيات المختلفة توعية الاسرة عن طريق وسائل الاعلام المقروءة والمرئية والمسموعة بمدى فاعلية واهمية برامج وخدمات المراكز والجمعيات المختلفة التي تخدم الاسرة القاء الضوء على المعوقات التي تحد من فاعلية برامج وخدمات المراكز والجمعيات المختلفة
The study aims to identify to identify the extent of the family's awareness and how they benefit from the programs, activities and services centers and various associations that serve the family, the detection of the correlation between family awareness of the existence of services provided by the centers and various associations and benefit from the programs, activities and services provided by the centers and various associations, has applied Tools The study "public data form, and family awareness of how they benefit from the programs, activities and services centers and various associations that serve the family questionnaire" on the sample and strength (230) family of different social and economic levels The study found: • The high level of awareness of the existence of services provided by the centers was representing the proportion of 29.1%, while the level of average awareness of the services provided by the centers was representing the proportion of 48.3%, while the low level of awareness of the existence of services provided by the centers was a ratio of 22.6%, as can be seen from the table and figure chart that take advantage of the high level of services provided by the centers were accounting for 37.8%, while the average utilization level of services provided by the centers were accounting for 41.3%, while the low level of utilization of services provided by the centers were accounting for 20.9%. • statistically significant differences between respondents in the awareness of the existence of services provided by the centers and various associations depending on the variables of the study "Social status differences, the education of husband and wife, the age of the wife, the wife's work, the monthly income of the family", was in favor of the single function, and educational level of the husband and wife, and for the life of the greatest , and the wives of workers, and family members with an average income. • statistically significant differences between respondents to benefit from the programs, activities and services provided by the centers and various associations depending on the variables of the study "Social status differences, the education of husband and wife, the age of the wife, the wife's work, the monthly income of the family", was in favor of the single function, and educational level of the husband and wife , and for the life of the greatest, and the wives of the workers, and family members and low-income. • There is a direct correlation between the family awareness of the existence of services provided by the various centers, associations and benefit from the programs, activities and services provided by the various centers and associations. • the participation rate of the factors affecting the family awareness of the existence of different services offered by the various centers and associations, where he was teaching the wife ranked first, followed by the age of the wife in second place, and then teach the pair in third place and, finally, the monthly income of the household in the last rank. • the participation rate of the factors affecting the family take advantage of the programs, activities and services provided by the centers and various associations, where he was teaching the pair ranked first, followed by education wife in second place differ, then the age of the wife in third place, and finally the monthly income of a family in last place. The study recommended that: • hold educational seminars and training sessions to raise awareness of the importance of family benefit from their various centers and associations. • Family awareness through the print media and broadcast the effectiveness and the importance of programs and services centers and various associations that serve the family. • shed light on the obstacles that limit the effectiveness of programs and services centers and various associations.
Keywords: الأسرة -- الخدمة الإجتماعية -- المراكز الإجتماعية -- الوعى الأسرى -- التنمية الأسرية